Jonas and Kovner's health care delivery in the United States - Knickman, James; Kovner, Anthony R.; Jonas, Steven (Springer Publishing Company, LLC, 2015)
"Health care managers, practitioners, and students must both operate as effectively as they can within the daunting and continually evolving system at hand and identify opportunities for reform advances ... Health Care Delivery in the United States has been an indispensable companion to those preparing to manage this balance. The present edition demonstrates once again why this volume has come to be so prized. It takes the long view - charting recent developments in health policy, and putting them side-by-side with descriptions and analysis of existing programs in the United States and abroad."